Ensuring Personal Data Protection in Telemedicine Services - Destyarini, Normalita (Faculty of Law, Universitas Jenderal Soedirman, 2024)
The development of technology utilization in terms of the business sector in various fields makes its own challenges in providing consumer protection. then it is necessary to know that the Personal Data Protection of telemedicine service users provides consumer protection accommodation. There are aspects of protection for consumers as service users of personal data. Control of personal data should be carried out by companies that use technology in their business activities, in this case the organizers of electronic systems as required by existing regulations. The protection of consumers has been accommodated in the Consumer Protection Law (1999). Problems with data leaks that occur in Indonesia are problems experienced by consumers as users of digital services. Protection of personal data is a basic right of citizens and therefore the role of the State as the competent authority in the management and regulation of personal data. To ensure accommodation of personal data protection in the business development of digital start-up companies, it is necessary to study the accommodation of personal data protection as a form of protection for consumers in the Consumer Protection Law ( 1999) by Digital Start-up Companies as service providers. Normative research method with conceptual and legal approach is used to explain the facts. The results of this study show that the Consumer Protection Law (1999) on Consumer Protection has not provided regulatory accommodation that provides data protection for consumers of telemedicine. Output from this research can be a guideline for consumer protection practices in digital start-ups as required by the Consumer Protection Law (1999) and recommendations for relevant stakeholders in digital start-up services.Keywords: Consumer Protection; Personal Data Protection; Start-Up.